2019
DOI: 10.1111/exd.13952
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of PD‐1 and Tim‐3 immune checkpoint receptors in patients with vitiligo; positive association with disease activity

Abstract: The contribution of immune checkpoint receptors in the immunopathogenesis of various autoimmune diseases has been addressed in previous reports. In this study,  the expression profile of T‐cell immunoglobulin and mucin‐domain containing‐3 (Tim‐3) and programmed cell death‐1 (PD‐1) checkpoint molecules was investigated in CD8+ T cells of Vitiligo patients. The association of Tim‐3 and PD‐1 expression with disease activity was also explored. The frequency of Tim‐3+/PD‐1+/CD8+ T cells in 30 patients with vitiligo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 51 publications
0
19
1
Order By: Relevance
“…Recently, programmed cell death protein (PD)‐1 and T‐cell immunoglobulin and mucin‐domain containing‐3 molecules, which serve as immune checkpoints to mediate braking of cytotoxic response, are found to be highly expressed on vitiligo CD8 + T cells. This is surmised to be a compensation mechanism of the immune system to keep peripheral tolerance towards self‐tissue, in face of hyperactivated CD8 + T cells 163 . A study administrating programmed death‐ligand 1 on vitiligo mice successfully reversed the depigmentation also endorses the participation of immune checkpoint in self‐immunoresponse against melanocytes 164 …”
Section: Adaptive Immune Activationmentioning
confidence: 99%
“…Recently, programmed cell death protein (PD)‐1 and T‐cell immunoglobulin and mucin‐domain containing‐3 molecules, which serve as immune checkpoints to mediate braking of cytotoxic response, are found to be highly expressed on vitiligo CD8 + T cells. This is surmised to be a compensation mechanism of the immune system to keep peripheral tolerance towards self‐tissue, in face of hyperactivated CD8 + T cells 163 . A study administrating programmed death‐ligand 1 on vitiligo mice successfully reversed the depigmentation also endorses the participation of immune checkpoint in self‐immunoresponse against melanocytes 164 …”
Section: Adaptive Immune Activationmentioning
confidence: 99%
“…A study of patients with metastatic melanoma showed that exosomes released from melanoma cells carry PD-L1 on their surface, and that the increase in levels of circulating exosomal PD-L1 correlates with tumor response to anti-PD-1 therapy [87]. In vitiligo, PD-1 expression in CD8+ T cells is positively associated with disease activity [90].…”
Section: Micrornas (Mirnas)mentioning
confidence: 99%
“…PD-L1 expression by autoreactive T cells, however, has not been shown. Similarly, vitiligo patients show increased PD-1 expression on CD8 + T cells compared to healthy donor CD8 + T cells ( 47 ), implying that PD-1 expression is due to excessive activation of autoreactive CD8 + T cells. PD-1 expression on CD8 + T cells appears to positively correlate with disease activity ( 47 ), suggesting a more vigorous attempt to control the inflammatory situation by increasing PD-1 expression.…”
Section: Pd-1/pd-l1 In Vitiligomentioning
confidence: 99%
“…Similarly, vitiligo patients show increased PD-1 expression on CD8 + T cells compared to healthy donor CD8 + T cells ( 47 ), implying that PD-1 expression is due to excessive activation of autoreactive CD8 + T cells. PD-1 expression on CD8 + T cells appears to positively correlate with disease activity ( 47 ), suggesting a more vigorous attempt to control the inflammatory situation by increasing PD-1 expression. In situ , PD-1 is significantly expressed in marginal and lesional infiltrates when compared to non-lesional skin in patients with active non-segmental vitiligo ( 48 ).…”
Section: Pd-1/pd-l1 In Vitiligomentioning
confidence: 99%